2020
DOI: 10.33259/jlivestsci.2020.85-89
|View full text |Cite
|
Sign up to set email alerts
|

The influence of antioxidant on the productivity and activity of digestive broiler enzymes in reducing the risk of T-2 toxin

Abstract: Recently, positive results have been achieved to reduce the risk of mycotoxicosis in meat poultry by rational use of various feed antioxidants, which inhibit processes of lipid peroxidation in the body and increase its immunity. The research aims to study the effect of different dosages of feed antioxidant Epofen on the basic economic and useful performance and digestive enzyme activity of broiler chickens grown on wheat-sorghumsunflower-based diets with tolerance level of T-2 toxin. To achieve this aim, the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 3 publications
(3 reference statements)
1
1
0
Order By: Relevance
“…The mixture of preparations mold inhibitor Myсo Сurb and adsorbent ALNI-SORB had the greatest promoting effect on the activity of amylolitic enzymes in the digestive tract of boilers from the third test group, which allowed them to surpass in amylases activity of the gizzard stomach content by 14.7% as well as duodenumby 18.4%, respectively. Our data are consistent with the results of researchers who experimentally found that when the natural adsorbent zeolite is included in broiler diets, the enzymes of proteinases, amylases and cellulases are activated in the chyme of the small intestine (Kairov et al, 2020).…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…The mixture of preparations mold inhibitor Myсo Сurb and adsorbent ALNI-SORB had the greatest promoting effect on the activity of amylolitic enzymes in the digestive tract of boilers from the third test group, which allowed them to surpass in amylases activity of the gizzard stomach content by 14.7% as well as duodenumby 18.4%, respectively. Our data are consistent with the results of researchers who experimentally found that when the natural adsorbent zeolite is included in broiler diets, the enzymes of proteinases, amylases and cellulases are activated in the chyme of the small intestine (Kairov et al, 2020).…”
Section: Resultssupporting
confidence: 93%
“…The harmful effect of feed, affected by fungal microflora, on the poultry body is associated with the presence of toxic substances arising when feed is affected during storage by microscopic fungi Aspergilius, Penicilium, etc. Among mycotoxins, aflatoxins produced by microscopic fungi Aspergilius flavus and Aspergilius parasitikus are provided by their toxic, carcinogenic and mutative properties Kairov et al, 2020;Temiraev et al, 2011;Tsalieva et al, 2017).…”
Section: Introductionmentioning
confidence: 99%